Relation between friction stir spot welding parameters and mechanical properties of high density polyethylene/glass spheres polymer composites - (:unkn) unknown (Trans Tech Publications Ltd, 2016)
In the present study, we attempt to use powder of glass spheres filler and reinforce material in HDPE to produce composite structure and then evaluate its mechanical properties to study the effect of welding parameters and filler content on mechanical properties of HDPE. The effect of welding parameters (tool rotational speed, the plunge depth and the dwell time) on friction stir spot welding properties of high density polyethylene/glass spheres (hollow) polymer composites sheets was studied. © 2016 Trans Tech Publications, Switzerland.
Keywords: Friction stir spot welding; Glass spheres; High density polyethylene; Polymer composites